Evaluation of Cathra system for identifying gram negative aerobic bacteria. - Ling, J M (J Clin Pathol, 1990)
The Cathra system is a commercial multipoint inoculation method for the identification of aerobic Gram negative bacteria. The system uses a replicator technique in which 21 different agar media can be inoculated simultaneously with 36 organisms. Identifications are made by use of a special computer database. The performance of this system was compared with that of the API 20E for the identification of 372 clinical isolates of Enterobacteriaceae and 133 miscellaneous Gram negative bacteria. For enterobacteria, the Cathra system was in 97% agreement with API 20E at species level and 98% at genus level. For miscellaneous Gram negative strains the two systems were in 59% agreement at species level and 77% at genus level. The Cathra system is suitable for use in diagnostic laboratories, especially those with a heavy workload and a wish to use break-point sensitivity testing. The identification database for miscellaneous Gram negative organisms, however, needs to be expanded.